Nano-Encapsulation Of Neem Based Pesticide Formulations (Journal of Plant Disease Sciences, 2023)
Neem based pesticide formulations are reported to control plant parasitic fungi, bacteria, virus, nematodes, insects and mites. Despite its many promising properties, low stability under field conditions, mainly due to a high rate of photo-degradation, as well as a short residence time and slow killing rates, compared to conventional pesticides hinder effective large-scale use of Neem. Although when two lines of Myzus persicae Were exposed to pure azadirachtin and refined Neem seed extract at the same concentration, it was found that after forty generations, the line treated with azadirachtin had developed ninefold greater resistance compared to a control line, whereas the line treated with the extract did not show resistance. To overcome these limitations, nanotechnology has emerged as a novel tool for agricultural sustainability. Many studies have shown that the encapsulation of agrochemicals in nanoparticulate systems can enhance the efficacy of the active ingredient, decrease toxicity toward the environment and humans, and reduce losses due to volatilization, leaching, and photobleaching. Thus, the use of nanoparticles provides an effective means of protecting neem oil against premature degradation, resulting in prolongation of its effect on the target pest. Due to nano encapsulation sustained release of the active component is achieved. Furthermore, the number of applications of neem oil can be reduced, bringing substantial economic benefits. Therefore, nano-encapsulation of neem oil may enable the production of more stable formulations for control of diseases and pests. Further, the use of nanotechnology is an excellent way to combat development of resistance in insects and pathogens due to indiscriminate use of neem oil.
Keywords: Azadirachta indica; Biopesticide; Nano-encapsulation